Evaluation of Straw Mushroom Color Stability during Storage: The Role of Nano Edible Coating, Packaging, and Temperature - Sitompul, Kiki Nuratni; Mubarok, Syariful; Kusumiyati, Kusumiyati (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Straw mushrooms are one of the nutritious edible mushrooms with high economic value. However, color changes during storage are one of the problems that impact the marketability. Post-harvest treatment in the form of the use of nano edible coatings, packaging, and storage temperatures can prevent gas exchange, control humidity and anti-browning agents in straw mushrooms. This study aims to evaluate the effect of nano edible coatings, packaging types, and different storage temperatures on the color stability of straw mushrooms. This study used a Completely Randomized Design consisting of a combination of nano edible coating treatments (nano sodium alginate and nano aloe vera), packaging types (vacuum, biodegradable, wrap packaging), and storage temperatures (room temperature (±25°C), 10°C, and 5°C), so that there are 18 treatment combinations. Each treatment was repeated twice so there were 36 experimental units. Each experimental unit consisted of two samples so that there were 72 samples at each observation time (1, 3, 5 days after storage), so that the total samples were 216. The results of the study showed that the combination treatment of nano sodium alginate with wrap packaging at a temperature of 10°C showed the best L*, a*, and hue values during 5 days of storage.